Moral Theology in the Ruins: Introducing a New Journal - David Matzko McCarthy (Journal of Moral Theology, 2012)
The establishment of this Journal of Moral Theology has as its aim to provide a solid grounding for critical discussion in order to navigate the modern moral issues in a fractured cultural and intellectual landscape, willing to interact with other disciplines such as political philosophy, psychology, and economics. While it may be tempting to turn to a “school of thought” methodology, such a lens proves inadequate for examining today’s moral questions and perpetuates, rather than heals, ruptures in the intellectual sphere; instead, JMT aims to suggest a common mode or theological imagination while also allowing a broad spectrum of views. It is a “coming down to earth’ in moral theology” rather than high, impractical abstractions, in and of itself a practice of the moral life.